INTRA-ANNUAL VARIABILITY IN THE INFESTATION OF THE CARIDEAN HIPPOLYTE ZOSTERICOLA SMITH, 1873. (CARIDEA: HIPPOLYTIDAE) BY THE PARASITIC ISOPOD BOPYRINA ABBREVIATA RICHARDSON, 1904 (EPICARIDEA: BOPYRIDAE) IN AN ESTUARINE SYSTEM IN THE SOUTHERN GULF OF MEXI - Rodríguez-Santiago, María (2020)
Th e aims of this study were to determine whether the prevalence of the parasitic isopod Bopyrina abbreviata Richardson,1904 in the decapod Hippolyte zostericola Smith, 1873, varies intra-annually in the estuarine lagoon system of the NaturalProtected Area Laguna de Terminos (Mexico) and whether this variability was related to changes in environmental conditions. Hippolyte zostericola collections were carried out (monthly during an annual cycle, 2011-2012) at three shallow sites of seagrass meadows (Th alassia testudinum Banks ex König, 1805). Th e environmental factors measured were water temperature, salinity, dissolved oxygen, pH, and rainfall. In general, the physicochemical data measured at the sampling sites were similar throughout the annual cycle (temperature: 30.6–25.8°C, salinity: 39.5–18.6 ups, dissolved oxygen: 9.6–5.4 mg L-1, pH: 8.7–8.2, rainfall: 240–5.4 mm). Of the total H. zostericola individuals examined (n = 116,002 individuals), 4.85% were infested by B. abbreviata. It was also found that there was variability in the prevalence between sites (S1 = 38% of the examined individuals; S2 = 2% and S3 = 7%). Th e greatest level of infestation by B. abbreviata occurred during the dry season (February –April), which was consistent with what was reported in a previous study. Th e results of a multiple regression analysis indicated that the environmental parameters that were signifi cantly correlated with the total monthly prevalence data of B. abbreviata were temperature, rainfall, and dissolved oxygen. The model resulting from this regression (prevalence = -397.92 + 12.12 temperature – 0.23 rainfall + 14.33 dissolved oxygen) explains 68.1% of the variability in the prevalence of B. abbreviata. This study contributes to the knowledge of the factors that can affect the spatio-temporal dynamics of the host-parasite relationship H. zostericola-B. abbreviata in shallow environments of seagrass meadows of the ANP Laguna de Terminos.